ANALISIS TRANSFORMASI GERAKAN SOSIAL POLITIK “BLACK LIVES MATTER” PADA TAHUN 2026 - Josua Sitanggang; Ardli Johan Kusuma; Saurma MGP Siahaan (Smart Education, 2026)
This research aims to analyze the transformation of the Black Lives Matter (BLM) socio-political movement in 2026 by answering the question of how the movement has transformed in the present era. This research uses a descriptive-explanatory qualitative approach with a literature review technique, which gathers data from academic journals and credible international media coverage. The analysis was conducted using the social movement theory formulated by Oman Sukmana (2016), which divides the life cycle of social movements into four stages: emergence, coalescence, bureaucratization, and decline. The research results show that BLM experienced an explosive emergence in 2020 as an accumulation of structural dissatisfaction with police violence triggered by the death of George Floyd, then entered the coalescence stage thru digital consolidation and the expansion of cross-issue coalitions, followed by the bureaucratization stage thru the establishment of the Black Lives Matter Global Network Foundation, which ironically harbors structural contradictions between institutional centralization and the grassroots decentralization tradition. At the decline stage, the movement faced a financial accountability crisis, political-structural pressure following the return of the Trump administration's anti-DEI policies, and a significant decrease in public support. This study concludes that the decline of BLM more reflects a pattern of group failure, but does not necessarily mark the permanent extinction of the movement, rather a redefinition of the struggle toward institutional consolidation and quieter legal advocacy.